Corrosion-resistant aluminum alloy rivet and preparation method thereof
By precisely controlling the alloy composition and optimizing the process, the corrosion-resistant aluminum alloy rivets prepared have solved the problems of insufficient corrosion resistance and mechanical properties of existing aluminum alloy rivets in complex environments. They have achieved high strength, low cracking rate and excellent corrosion resistance, meeting the high standards of aerospace, automobile manufacturing and shipbuilding industries.
Patent Information
- Application Number
- CN202511018189.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-23
- Publication Date
- 2025-11-11
AI Technical Summary
Existing aluminum alloy rivets are insufficient in terms of corrosion resistance, mechanical property stability, and forming qualification rate, making it difficult to meet the high standards required by complex industrial environments. They are particularly vulnerable to corrosion threats in the aerospace, automotive manufacturing, and shipbuilding industries, affecting the reliability and safety of the connection structure.
By precisely controlling the alloy composition ratio, combined with production process optimization, and employing component slow-release technology and improved wire drawing and heat treatment processes, corrosion-resistant aluminum alloy rivets are prepared. This includes boronizing treatment, uniform addition of multi-element alloy particles, grain refinement and formation of dispersed phases, optimization of casting and rolling processes, reduction of cracking rate and improvement of mechanical properties.
The prepared corrosion-resistant aluminum alloy rivets exhibit excellent corrosion resistance and high mechanical properties under complex working conditions, with tensile strength of 280-320MPa, yield strength ≥215MPa, elongation ≥18%, and cold heading cracking rate controlled below 10ppm, significantly improving the reliability and safety of the connection structure.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminum alloy rivet material technology, specifically to a corrosion-resistant aluminum alloy rivet and its preparation method. Background Technology
[0002] Aluminum alloy rivets, as structural connection components that combine lightweight and high strength, occupy an irreplaceable position in many fields such as aerospace, automotive manufacturing, and shipbuilding. Their excellent mechanical properties and connection stability make them a key element in ensuring the overall reliability of various complex structures. However, the complexity of industrial environments poses extremely stringent challenges to the performance of aluminum alloy rivets. In the aerospace field, rivets must withstand multiple tests, including high-altitude low-temperature environments, humidity changes, and airflow impacts. Vehicles in the automotive industry come into contact with corrosive media such as rainwater, oil, and salt during operation. Ships in the shipbuilding industry are constantly immersed in seawater or the humid marine atmosphere, facing even more severe corrosion threats. Under these harsh conditions, traditional aluminum alloy rivets are highly susceptible to surface oxidation, pitting, and crevice corrosion. This not only damages the appearance of the rivets but also significantly weakens their mechanical properties, posing a serious threat to the reliability and safety of the entire connection structure, potentially leading to equipment failure, structural failure, and other major risks.
[0003] Currently widely used 5-series aluminum alloy rivets present numerous problems in practical applications. These rivets are typically formed from aluminum alloy wire using a cold heading process, resulting in a cracking rate exceeding 10 ppm. This high cracking rate significantly reduces the rivet's pass rate, making it difficult to guarantee product performance stability. Furthermore, the presence of magnesium in the 5-series aluminum alloy composition makes it prone to compositional segregation, directly affecting key mechanical properties such as tensile strength, shear force, and elongation, thus failing to meet the application requirements of some high-precision and high-reliability scenarios. In addition, aluminum alloy rivets often come into direct contact with other structural components such as copper and steel during actual assembly. Due to the potential difference between different metals, electrochemical corrosion can easily occur under complex working conditions, further accelerating rivet damage, shortening their service life, increasing equipment maintenance costs, and creating safety hazards.
[0004] Existing aluminum alloy rivets have significant shortcomings in corrosion resistance, mechanical property stability, and forming yield, making them unsuitable for the increasingly complex industrial environment and its demanding requirements for structural connection components. Therefore, there is an urgent need to develop an aluminum alloy rivet with low cracking rate, excellent mechanical properties, and good corrosion resistance, which is of great significance for improving the reliability and safety of various connection structures. Summary of the Invention
[0005] To address the above technical problems, the present invention aims to provide a corrosion-resistant aluminum alloy rivet and its preparation method. By precisely controlling the alloy composition ratio and combining it with systematic optimization of the production process, and by improving the wire drawing process and subsequent heat treatment process, the elongation rate is significantly improved while ensuring the tensile strength of the aluminum alloy rivet. This effectively reduces the probability of cracking during the cold heading process and endows the aluminum alloy rivet with excellent corrosion resistance.
[0006] The above-mentioned objective of the present invention is achieved through the following technical solution:
[0007] A method for preparing a corrosion-resistant aluminum alloy rivet includes the following steps:
[0008] (1) The aluminum ingots are put into the melting furnace for melting and boronizing treatment, and the first aluminum liquid is obtained after one refining process;
[0009] (2) Transfer the first aluminum liquid obtained in step (1) to a heat preservation furnace, and add various aluminum-based alloy particles containing silicon (Si), iron (Fe), magnesium (Mg), manganese (Mn), chromium (Cr), zirconium (Zr), rare earth element cerium (Ce) and lanthanum (La) in proportion to obtain the second aluminum liquid;
[0010] (3) The second aluminum liquid obtained in step (2) is refined a second time to obtain the third aluminum liquid;
[0011] (4) Add aluminum-titanium-boron wire to the third aluminum liquid obtained in step (3), and obtain the fourth aluminum liquid after degassing and filtration;
[0012] (5) The fourth aluminum liquid obtained in step (4) is continuously cast under the conditions of casting temperature of 710-730℃, casting speed of 2.8-3.0t / h, cooling water temperature of 20-40℃ and billet temperature of 450-470℃ to obtain aluminum billet;
[0013] (6) The surface of the aluminum billet obtained in step (5) is treated by a milling machine to obtain the billet;
[0014] (7) Roll the billet obtained in step (6) at a rolling temperature of 400-450℃ and a take-off temperature of 180-220℃ to obtain a corrosion-resistant aluminum rod with a nominal diameter of 9.00±0.3mm.
[0015] (8) The corrosion-resistant aluminum rod with a nominal diameter of 9.00±0.3mm obtained in step (7) is subjected to a first drawing process to obtain a corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25±0.02mm;
[0016] (9) The corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25±0.02mm obtained in step (8) is heat-treated at 410-440℃ to obtain aluminum alloy wire.
[0017] (10) The aluminum alloy wire obtained in step (9) is subjected to a second drawing process to obtain an aluminum alloy wire with a nominal diameter of 6.10±0.02mm;
[0018] (11) After cutting the aluminum alloy wire with a nominal diameter of 6.10±0.02mm obtained in step (10), cold heading is performed to obtain the corrosion-resistant aluminum alloy rivet.
[0019] The corrosion-resistant aluminum alloy rivet contains 0.20-0.25wt% Si, 0.15-0.20wt% Fe, 4.3-4.5wt% Mg, 0.8-0.9wt% Mn, 0.10-0.15wt% Cr, 0.15-0.20wt% Zr, 0.1-0.2wt% Ce+La, 0.01-0.015wt% Ti, with the remainder being Al and unavoidable impurities, and the Si / Fe ratio is ≥1.
[0020] From a composition design perspective, multiple elements can refine grain size and improve corrosion resistance, but precise control of the proportions of each element is necessary. Simultaneously, interactions between elements (such as forming strengthening phases and inhibiting the precipitation of harmful phases) can also positively enhance alloy properties. Specifically:
[0021] Mg element: When the content is <4.3wt%, solid solution strengthening is insufficient, resulting in insufficient strength; when the content is 4.3-4.5wt%, the β phase (mainly referring to Mg2Al3 phase) is dispersed, avoiding the risk of intergranular corrosion caused by continuous precipitation; when the content is >4.5wt%, compared with the Mg content of 4.3-4.5wt%, the β phase precipitates continuously, forming corrosion channels, the hot cracking sensitivity increases by 30%, and the intergranular corrosion is aggravated.
[0022] Mn element: The content needs to be strictly controlled at 0.8-0.9wt%, and it works synergistically with Mg element (4.3-4.5wt%) to improve tensile strength and corrosion resistance. Its main functions include: (1) Optimizing grain structure: It can significantly increase the recrystallization temperature of aluminum alloy (by about 50-80℃), and hinder grain growth by forming a diffusely distributed Al6Mn compound, thus refining the grain by 30-50%; at the same time, for every 0.1wt% increase in Mn element, the tensile strength of the alloy increases by about 5-8MPa (achieved through solid solution strengthening and grain refinement strengthening). (2) Neutralizing impurities and reducing the harm of Fe: It forms (Fe,Mn)Al6 phase with Fe, replacing the acicular brittle β-AlFeSi phase, reducing the damage of Fe to ductility; forming stable compounds: The electrode potential of Al6Mn phase is close to that of aluminum matrix, avoiding the formation of galvanic corrosion source. (3) Promoting the formation of dense oxide film and enhancing the corrosion resistance of alloy.
[0023] Cr element: The content is 0.10-0.15wt%. It forms Al(Mn,Cr) dispersed phase together with Mn, which further inhibits grain boundary corrosion, synergistically refines grains, and improves tensile strength. It can also promote the formation of Al(Fe,Cr)Si stable phase of Si / Fe, reduce grain boundary corrosion channels, and enhance the anti-corrosion effect.
[0024] Zr element: The content is 0.15-0.20wt%. Zr forms nanoscale Al3Zr dispersed phase, which serves as a heterogeneous nucleation core, reducing the size of cast grains by 30%-50%. At the same time, the Al3Zr phase pins the grain boundaries, hindering grain growth during high-temperature deformation.
[0025] Rare earth elements (Ce+La): with a content of 0.1-0.2wt%. Rare earth elements can react with H, O, N and other elements in the melt to form stable compounds (such as CeH2, La2O3), which significantly reduces the pinhole rate; they can also adsorb low melting point impurities (such as Pb, Sn) to form high melting point slag phases and float them for removal; they can form (Fe,RE)Al6 phase with Fe to replace the brittle β-AlFeSi phase; they can inhibit the precipitation of coarse compounds such as Mg2Si, so that the second phase is uniformly dispersed; and they can also promote the formation of dense oxide film.
[0026] In addition, the Si / Fe ratio must be ≥1. When Fe and Si coexist and the ratio is unbalanced (Fe > Si), needle-like or plate-like β-AlFeSi phases (such as β-Al5FeSi) are easily formed, which will become stress concentration sources and significantly reduce the ductility and impact toughness of the alloy. When Si > Fe, it tends to form Chinese character-shaped α-AlFeSi phases (such as α-Al8Fe2Si), which have little impact on mechanical properties.
[0027] In a specific implementation, in step (1), aluminum ingots with a purity of not less than 99.7% are added to a melting furnace and heated to melt. An aluminum-boron alloy is added for boronizing treatment. Under the condition of holding at 750-780℃, a refining agent is blown in with nitrogen to perform a first refining process to obtain the first aluminum liquid.
[0028] Furthermore, the refining agent is a sodium removal refining agent.
[0029] Boration treatment allows element B to fully react with impurities such as V to form high-melting-point compounds, which can be effectively removed by slag removal.
[0030] Aluminum-boron alloy is used in the smelting furnace for boronizing treatment, which allows the reaction of elements such as boron (B) and impurity elements such as vanadium (V) to be complete and thorough. At the same time, the furnace is used for the first refining process to reduce the content of impurity elements and hydrogen in the aluminum melt.
[0031] Furthermore, in step (1), the content of the unavoidable impurities does not exceed 0.02 wt%.
[0032] Furthermore, in step (2), the temperature in the heat preservation furnace is 720-740℃.
[0033] Furthermore, in step (2), the aluminum-based alloy particles are obtained by melting and granulating an aluminum-based master alloy.
[0034] Furthermore, in step (2), the particle size of the aluminum-based alloy particles is 5-10 mm.
[0035] In a specific implementation, in step (2), the first aluminum liquid obtained in step (1) is transferred to a holding furnace at 720-740°C, and after standing for 20-30 minutes, a sample is taken and the composition is detected by a direct-reading spectrometer. The corresponding aluminum-based alloy particles are added to the holding furnace in a certain proportion, and after stirring and standing, the second aluminum liquid is obtained.
[0036] The particle size of aluminum-based alloy particles affects the yield, melting efficiency and composition uniformity. When the particle size is less than 5 mm, the aluminum-based alloy particles tend to float on the surface of the molten aluminum, reducing the yield. When the particle size is large, it is easy to cause local enrichment of Si element, resulting in eutectic segregation, which in turn leads to the aggravation of cracking of some rivets.
[0037] This invention employs a component-controlled release technology. Its core principle involves preparing an aluminum-based master alloy into granular particles with a diameter of 5-10 mm. The uniform release and precise control of alloying elements are achieved through the gradual melting process of these particles in molten aluminum. In traditional processes, directly adding powdered or block-shaped master alloys can easily lead to a rapid increase in local element concentration due to excessively fast melting, causing eutectic segregation or the concentrated precipitation of brittle phases (such as needle-like β-AlFeSi). However, the aluminum-based alloy particles of this invention (containing Si, Fe, Mg, Mn, Cr, Zr, and rare earth elements) exhibit a gradient melting effect in molten aluminum in a holding furnace at 720-740℃ due to the temperature difference between the particle surface and the molten aluminum. The outer layer of the particles melts and releases elements first, while the inner layer dissolves slowly over time, with the entire melting process lasting 20-30 minutes. This "stepwise dissolution" mechanism allows for more sufficient diffusion time for each element in the molten aluminum, controlling concentration fluctuations within ±5%, and effectively avoiding localized component imbalances.
[0038] Furthermore, in step (3), the temperature of the secondary refining is 720-740℃.
[0039] In a specific implementation, in step (3), after the composition of the second aluminum liquid is qualified, argon gas is used to blow in the refining agent for the second refining. After standing, the slag is removed, and it is stood for another 30-40 minutes to obtain the third aluminum liquid.
[0040] Furthermore, in step (4), 1.5-2.0 kg of aluminum-titanium-boron wire is added per ton of third aluminum liquid.
[0041] In a specific embodiment, in step (4), the third aluminum liquid in the heat preservation furnace is poured into the flow channel, and aluminum titanium boron (AlTi5B1) wire is fed before entering the degassing box. Then, it is degassed and filtered in sequence through the degassing box and the filter box to obtain the fourth aluminum liquid.
[0042] After adding AlTi5B1 wire, Ti significantly refines the as-cast grains and improves the strength and toughness of the alloy by forming fine TiAl3 or TiB2 compounds as heterogeneous nucleation cores. At the same time, Ti promotes the formation of a denser Al2O3-TiO2 composite oxide film on the surface of the aluminum alloy, reducing corrosion efficiency.
[0043] This invention, through experiments and optimization of smelting and casting temperatures, confirmed that a smelting temperature of 720-740℃ is most suitable, and a casting temperature of 710-730℃ is optimal. When the casting temperature is below 710℃, the aluminum melt has poor fluidity and contains more inclusions; when the casting temperature is above 740℃, Mg burn-off intensifies, the grains become coarser, and the number of subsequent cold heading cracks increases.
[0044] In a specific implementation, in step (6), a milling machine is used to remove burrs, cracks, shrinkage cavities, and oxide scale from the surface of the aluminum billet obtained in step (5), thus avoiding defects in the subsequent rolling process and obtaining the billet. The core purpose of step (6) is to provide a clean and flat surface foundation for the subsequent rolling process, and to prevent defects from being amplified or transmitted to the final product during the rolling process.
[0045] Furthermore, step (7) also includes a step of lubricating and cooling the aluminum rod and the rolling mill by means of the flow rate and pressure of the emulsion during the rolling process.
[0046] In a specific implementation, in step (7), the billet obtained in step (6) is rolled at a rolling temperature of 400-450°C. During the rolling process, the aluminum rod and the rolling mill are lubricated and cooled by the flow rate and pressure of the emulsion. The rolled aluminum rod is immediately water-cooled and the rod temperature is 180-220°C. After the aluminum rod is taken off the production line, it is cooled to room temperature by a fan to obtain a corrosion-resistant aluminum rod with a nominal diameter of 9.00±0.3mm.
[0047] Furthermore, in step (8), a four-pass die-fitting scheme is adopted in the first drawing process, with a cross-sectional compression rate of 17-19% for each pass.
[0048] In a specific implementation, in step (8), the corrosion-resistant aluminum rod with a nominal diameter of 9.00 mm obtained in step (7) is first drawn using a four-pass die matching scheme. The four-pass die matching scheme is 9.00-8.20-7.45-6.75-6.25 mm, resulting in a corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25 mm.
[0049] Furthermore, in step (9), the heat treatment time is 6-8 hours.
[0050] In a specific embodiment, in step (9), the corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25±0.02mm obtained in step (8) is heat-treated at 410-440℃, kept at the temperature for 6-8 hours, and then air-cooled to room temperature to obtain the aluminum alloy wire.
[0051] This invention systematically explored and optimized the heat treatment process, and determined a process scheme of 410-440℃, heat treatment for 6-8 hours followed by air cooling, which enabled the preparation of medium-strength corrosion-resistant rivets, while effectively reducing the cracking rate of rivets.
[0052] When the heat treatment temperature is below 410℃, the diffusion rate of elements such as Mg, Mn, and Cr is insufficient, failing to fully form dispersed strengthening phases such as Al6Mn and Al(Mn,Cr). Furthermore, the solid solubility of Mg in the Al matrix decreases, leading to a weakened solid solution strengthening effect and ultimately a reduction in the tensile strength of the wire. When the temperature exceeds 440℃, the already formed fine strengthening phases (such as Al3Zr) coarsen, and Mg elements tend to aggregate at grain boundaries to form a continuous β phase, increasing the alloy's brittleness. Although the tensile strength may increase in the short term, the elongation will drop below 15%, significantly increasing the risk of cracking during cold heading. The temperature range of 410-440℃ allows for precise control of the size and distribution density of the strengthening phases, ensuring both the dispersed precipitation of phases such as Al6Mn and avoiding the continuous precipitation of the β phase.
[0053] When the holding time is less than 6 hours, the strengthening phase precipitation is insufficient, the synergistic effect of solid solution strengthening and fine grain strengthening is weak, and the tensile strength is difficult to reach 280 MPa. When the holding time exceeds 8 hours, the strengthening phase (such as Al6Mn) will grow too long due to excessive growth, which weakens its hindering effect on dislocations and reduces the tensile strength. At the same time, the segregation of Mg elements at the grain boundaries is intensified, reducing the yield strength. A holding time of 6-8 hours can achieve a dynamic balance between the "precipitation-stabilization" of the strengthening phase. Combined with the air cooling process, it can suppress the formation of coarse phases, ultimately enabling the wire to maintain high tensile strength while also having high elongation.
[0054] Furthermore, in step (10), the aluminum alloy wire with a nominal diameter of 6.10±0.02mm has a tensile strength of 280-320MPa, a yield strength of ≥215MPa, and an elongation of ≥18%.
[0055] In a specific implementation, in step (11), the aluminum alloy wire with a nominal diameter of 6.10±0.02mm obtained in step (10) is fed into a straightening machine for processing, then cut into a blank of 22.0±0.5mm, burrs are removed, and the blank is sent into a cold heading machine for stamping to obtain a corrosion-resistant aluminum alloy rivet.
[0056] This invention also protects a corrosion-resistant aluminum alloy rivet prepared by the above-described preparation method.
[0057] The beneficial effects of this invention are:
[0058] 1. This invention innovatively employs a component slow-release technology to prepare aluminum-based master alloys into aluminum-based alloy particles. This technology ensures that alloying elements such as Si, Mg, and rare earth elements are uniformly distributed in molten aluminum, effectively avoiding performance defects caused by local concentration imbalances, thereby significantly improving the mechanical properties and product consistency of aluminum alloys. Simultaneously, active elements (such as Mg) existing in granular form exhibit greater stability, reducing oxidation and burn-off caused by high temperatures during direct addition, ensuring that elements are precisely integrated into the alloy system according to the designed proportions, and greatly optimizing the efficiency of component control.
[0059] 2. The corrosion-resistant aluminum alloy rivets prepared by this invention have both excellent mechanical properties and corrosion resistance. The aluminum alloy wire with a nominal diameter of 6.10±0.02mm has a tensile strength of 280-320MPa, a yield strength of not less than 215MPa, and an elongation of not less than 18%. Moreover, the cracking rate during the cold heading process is controlled below 10ppm. The comprehensive performance indicators are significantly better than those of traditional aluminum alloy rivets, and can meet the high standard requirements for connecting parts under complex working conditions. Detailed Implementation
[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0061] The present invention will be further described below with reference to specific embodiments, so that those skilled in the art can better understand and implement the present invention, but the embodiments are not intended to limit the present invention.
[0062] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used are commercially available.
[0063] Example 1
[0064] A method for preparing a corrosion-resistant aluminum alloy rivet includes the following steps:
[0065] (1) Add aluminum ingots with a purity of not less than 99.7% into a smelting furnace and heat to melt. Add aluminum-boron alloy for boronizing treatment. Under the condition of holding at 765℃, refine the first aluminum liquid by blowing in refining agent with nitrogen.
[0066] (2) The first aluminum liquid was transferred to a holding furnace at 730°C and left to stand for 25 minutes. The sample was then taken and the composition was detected by SPECTROCHECK direct reading spectrometer. Aluminum-based alloy particles with a particle size of 8 mm containing silicon, iron, magnesium, manganese, chromium, zirconium and rare earth elements (La, Ce) were added to the holding furnace in a certain proportion. After stirring and standing, the second aluminum liquid was obtained.
[0067] (3) After the composition of the second aluminum liquid is qualified, the refining agent is blown in with argon gas and the second refining is carried out at 730°C. After standing, the slag is removed and the liquid is left to stand for 35 minutes to obtain the third aluminum liquid.
[0068] (4) Pour the third aluminum liquid in the heat preservation furnace into the flow channel. Before entering the degassing box, feed AlTi5B1 wire at an addition rate of 1.6 kg / t. Then, degas and filter the aluminum liquid in sequence through the degassing box and the filter box to obtain the fourth aluminum liquid.
[0069] (5) The fourth aluminum liquid was continuously cast under the conditions of casting temperature of 720℃, casting speed of 2.9t / h, cooling water temperature of 30℃ and billet temperature of 460℃ to obtain aluminum billet.
[0070] (6) Use a milling machine to cut off the flash, burrs, cracks, shrinkage and oxide scale on the surface of the aluminum billet to avoid defects in the subsequent rolling process and obtain the billet.
[0071] (7) The billet is rolled at a rolling temperature of 425°C. During the rolling process, the aluminum rod and the rolling mill are lubricated and cooled by the flow rate and pressure of the emulsion. The rolled aluminum rod is immediately water-cooled and the rod temperature is 200°C. After the aluminum rod is taken off the line, it is cooled to room temperature by a fan to obtain a corrosion-resistant aluminum rod with a nominal diameter of 9.00 mm.
[0072] (8) The corrosion-resistant aluminum rod with a nominal diameter of 9.00 mm was first drawn using a four-pass die matching scheme. The four-pass die matching scheme is 9.00-8.20-7.45-6.75-6.25 mm, resulting in a corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25 mm.
[0073] (9) A corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25 mm was heat-treated at 410°C, held at the temperature for 7 hours, and then air-cooled to room temperature to obtain the aluminum alloy wire.
[0074] (10) The aluminum alloy wire is subjected to a second drawing process to obtain an aluminum alloy wire with a nominal diameter of 6.10 mm.
[0075] (11) After the aluminum alloy wire with a nominal diameter of 6.10 mm is fed into the straightening machine for processing, it is cut into a blank of 22.0 mm, the burrs are removed, and it is sent into the cold heading machine for stamping to obtain corrosion-resistant aluminum alloy rivets.
[0076] The composition of the corrosion-resistant aluminum alloy rivets was tested and found to be: Si 0.22wt%, Fe 0.18wt%, Mg 4.40wt%, Mn 0.85wt%, Cr 0.12wt%, Zr 0.17wt%, Ce+La 0.15wt%, Ti 0.012wt%, with the remainder being Al and unavoidable impurities (impurities not exceeding 0.02wt%).
[0077] Example 2
[0078] A method for preparing a corrosion-resistant aluminum alloy rivet includes the following steps:
[0079] (1) Add aluminum ingots with a purity of not less than 99.7% into a smelting furnace and heat to melt. Add aluminum-boron alloy for boronizing treatment. Under the condition of holding at 750℃, refine the first aluminum liquid by blowing in refining agent with nitrogen.
[0080] (2) The first aluminum liquid was transferred to a holding furnace at 720°C and left to stand for 20 minutes. The sample was then taken and the composition was detected by SPECTROCHECK direct reading spectrometer. Aluminum-based alloy particles with a particle size of 5 mm containing silicon, iron, magnesium, manganese, chromium, zirconium and rare earth elements (La, Ce) were added to the holding furnace in a certain proportion. After stirring and standing, the second aluminum liquid was obtained.
[0081] (3) After the composition of the second aluminum liquid is qualified, the refining agent is blown in with argon gas and the second refining is carried out at 720°C. After standing, the slag is removed and the liquid is left to stand for 30 minutes to obtain the third aluminum liquid.
[0082] (4) Pour the third aluminum liquid in the heat preservation furnace into the flow channel. Before entering the degassing box, feed AlTi5B1 wire at an addition rate of 1.6 kg / t. Then, degas and filter the aluminum liquid in sequence through the degassing box and the filter box to obtain the fourth aluminum liquid.
[0083] (5) The fourth aluminum liquid was continuously cast under the conditions of casting temperature of 710℃, casting speed of 2.8t / h, cooling water temperature of 20℃ and billet temperature of 450℃ to obtain aluminum billet.
[0084] (6) Use a milling machine to cut off the flash, burrs, cracks, shrinkage and oxide scale on the surface of the aluminum billet to avoid defects in the subsequent rolling process and obtain the billet.
[0085] (7) The billet is rolled at a rolling temperature of 400°C. During the rolling process, the aluminum rod and the rolling mill are lubricated and cooled by the flow rate and pressure of the emulsion. The rolled aluminum rod is immediately water-cooled and the rod temperature is 180°C. After the aluminum rod is taken off the line, it is cooled to room temperature by a fan to obtain a corrosion-resistant aluminum rod with a nominal diameter of 9.00 mm.
[0086] (8) The corrosion-resistant aluminum rod with a nominal diameter of 9.00 mm was first drawn using a four-pass die matching scheme. The four-pass die matching scheme is 9.00-8.20-7.45-6.75-6.25 mm, resulting in a corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25 mm.
[0087] (9) A corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25 mm was heat-treated at 425°C, held at the temperature for 6 hours, and then air-cooled to room temperature to obtain the aluminum alloy wire.
[0088] (10) The aluminum alloy wire is subjected to a second drawing process to obtain an aluminum alloy wire with a nominal diameter of 6.10 mm.
[0089] (11) After the aluminum alloy wire with a nominal diameter of 6.10 mm is fed into the straightening machine for processing, it is cut into a blank of 22.0 mm, the burrs are removed, and it is sent into the cold heading machine for stamping to obtain the corrosion-resistant aluminum alloy rivet.
[0090] The composition of the corrosion-resistant aluminum alloy rivets was tested and found to be: Si 0.20wt%, Fe 0.15wt%, Mg 4.30wt%, Mn 0.80wt%, Cr 0.10wt%, Zr 0.15wt%, Ce+La 0.10wt%, Ti 0.010wt%, with the remainder being Al and unavoidable impurities (impurities not exceeding 0.02wt%).
[0091] Example 3
[0092] A method for preparing a corrosion-resistant aluminum alloy rivet includes the following steps:
[0093] (1) Add aluminum ingots with a purity of not less than 99.7% into a smelting furnace and heat to melt. Add aluminum-boron alloy for boronizing treatment. Under the condition of holding at 780℃, refine the first aluminum liquid by blowing in refining agent with nitrogen.
[0094] (2) The first aluminum liquid was transferred to a holding furnace at 740°C and left to stand for 30 minutes. The sample was then taken and the composition was detected by SPECTROCHECK direct reading spectrometer. A certain proportion of aluminum-based alloy particles with a particle size of 10 mm containing silicon, iron, magnesium, manganese, chromium, zirconium and rare earth elements (La, Ce) were added to the holding furnace. After stirring and standing, the second aluminum liquid was obtained.
[0095] (3) After the composition of the second aluminum liquid is qualified, the refining agent is blown in with argon gas and the second refining is carried out at 740°C. After standing, the slag is removed and the liquid is left to stand for 40 minutes to obtain the third aluminum liquid.
[0096] (4) Pour the third aluminum liquid in the heat preservation furnace into the flow channel. Before entering the degassing box, feed AlTi5B1 wire at an addition rate of 1.6 kg / t. Then, degas and filter the aluminum liquid in sequence through the degassing box and the filter box to obtain the fourth aluminum liquid.
[0097] (5) The fourth aluminum liquid was continuously cast under the conditions of casting temperature of 730℃, casting speed of 3.0t / h, cooling water temperature of 40℃ and billet temperature of 470℃ to obtain aluminum billet.
[0098] (6) Use a milling machine to cut off the flash, burrs, cracks, shrinkage and oxide scale on the surface of the aluminum billet to avoid defects in the subsequent rolling process and obtain the billet.
[0099] (7) The billet is rolled at a rolling temperature of 450°C. During the rolling process, the aluminum rod and the rolling mill are lubricated and cooled by the flow rate and pressure of the emulsion. The rolled aluminum rod is immediately water-cooled and the rod temperature is 220°C. After the aluminum rod is taken off the line, it is cooled to room temperature by a fan to obtain a corrosion-resistant aluminum rod with a nominal diameter of 9.00 mm.
[0100] (8) The corrosion-resistant aluminum rod with a nominal diameter of 9.00 mm was first drawn using a four-pass die matching scheme. The four-pass die matching scheme is 9.00-8.20-7.45-6.75-6.25 mm, resulting in a corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25 mm.
[0101] (9) A corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25 mm was heat-treated at 440°C, kept at the temperature for 8 hours, and then air-cooled to room temperature to obtain the aluminum alloy wire.
[0102] (10) The aluminum alloy wire is subjected to a second drawing process to obtain an aluminum alloy wire with a nominal diameter of 6.10 mm.
[0103] (11) After the aluminum alloy wire with a nominal diameter of 6.10 mm is fed into the straightening machine for processing, it is cut into a blank of 22.0 mm, the burrs are removed, and it is sent into the cold heading machine for stamping to obtain the corrosion-resistant aluminum alloy rivet.
[0104] The composition of the corrosion-resistant aluminum alloy rivets was tested and found to be: Si 0.25wt%, Fe 0.20wt%, Mg 4.50wt%, Mn 0.90wt%, Cr 0.15wt%, Zr 0.20wt%, Ce+La 0.20wt%, Ti 0.015wt%, with the remainder being Al and unavoidable impurities (impurities not exceeding 0.02wt%).
[0105] Comparative Example 1
[0106] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that in step (2), the amount of various aluminum-based alloy particles is adjusted.
[0107] The composition of the aluminum alloy rivet was determined to be: Si 0.18wt%, Fe 0.22wt%, Mg 4.40wt%, Mn 0.85wt%, Cr 0.12wt%, Zr 0.17wt%, Ce+La 0.15wt%, Ti 0.012wt%, with the remainder being Al and unavoidable impurities (impurities not exceeding 0.02wt%).
[0108] Comparative Example 2
[0109] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that in step (2), the amount of various aluminum-based alloy particles is adjusted.
[0110] The composition of the aluminum alloy rivet was determined to be: Si 0.22wt%, Fe 0.18wt%, Mg 5.02wt%, Mn 0.85wt%, Cr 0.12wt%, Zr 0.17wt%, Ce+La 0.15wt%, Ti 0.012wt%, with the remainder being Al and unavoidable impurities (impurities not exceeding 0.02wt%).
[0111] Comparative Example 3
[0112] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that in step (2), the amount of various aluminum-based alloy particles is adjusted.
[0113] The composition of the aluminum alloy rivet was determined to be: Si 0.22wt%, Fe 0.18wt%, Mg 3.91wt%, Mn 0.85wt%, Cr 0.12wt%, Zr 0.17wt%, Ce+La 0.15wt%, Ti 0.012wt%, with the remainder being Al and unavoidable impurities (impurities not exceeding 0.02wt%).
[0114] Comparative Example 4
[0115] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that: in step (2), the amount of various aluminum-based alloy particles is adjusted; and in step (4), aluminum-titanium-boron wire is not fed in.
[0116] The composition of the aluminum alloy rivet was tested and found to be: Si 0.22wt%, Fe 0.18wt%, Mg 4.40wt%, Mn 0.85wt%, Cr 0.12wt%, Zr 0.17wt%, with the remainder being Al and unavoidable impurities (impurities not exceeding 0.02wt%).
[0117] Comparative Example 5
[0118] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that in step (2), the amount of various aluminum-based alloy particles is adjusted.
[0119] The composition of the aluminum alloy rivet was determined to be: Si 0.22wt%, Fe 0.18wt%, Mg 4.40wt%, Mn 1.02wt%, Cr 0.12wt%, Zr 0.17wt%, Ce+La 0.15wt%, Ti 0.012wt%, with the remainder being Al and unavoidable impurities (impurities not exceeding 0.02wt%).
[0120] Comparative Example 6
[0121] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that in step (2), the amount of various aluminum-based alloy particles is adjusted.
[0122] The composition of the aluminum alloy rivet was determined to be: Si 0.22wt%, Fe 0.18wt%, Mg 4.40wt%, Mn 0.40wt%, Cr 0.12wt%, Zr 0.17wt%, Ce+La 0.15wt%, Ti 0.012wt%, with the remainder being Al and unavoidable impurities (impurities not exceeding 0.02wt%).
[0123] Comparative Example 7
[0124] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that in step (5), the casting temperature is 680℃.
[0125] Comparative Example 8
[0126] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that step (6) is not performed.
[0127] Comparative Example 9
[0128] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that the heat treatment temperature in step (9) is 360°C.
[0129] Comparative Example 10
[0130] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that the heat treatment temperature in step (9) is 450°C.
[0131] Comparative Example 11
[0132] A method for preparing an aluminum alloy rivet is basically the same as that in Example 1, except that in step (2), the aluminum-based alloy particles are replaced with an aluminum-based intermediate alloy.
[0133] Test case
[0134] The aluminum alloy wires with a nominal diameter of 6.10 mm prepared in Examples 1-3 and Comparative Examples 1-11 were subjected to performance tests. The tensile strength, yield strength, and elongation were tested according to GB / T 3195-2023 standard, and the corrosion resistance was tested according to GB / T 10125-2021 standard (neutral salt spray test). The cracking rate during the cold heading process was also tested.
[0135] The test results are shown in Table 1:
[0136] Table 1
[0137]
[0138]
[0139]
[0140] As can be seen from Table 1, compared with the remaining 11 comparative examples, the three experimental examples all had tensile strength > 300 MPa, yield strength > 220 MPa, elongation > 20%, and cold heading cracking rate < 10 ppm, showing the best corrosion resistance.
[0141] The various components in the aluminum alloy of this invention have synergistic effects. First, to ensure the strength of the rivet, the range of Mg element was determined. Compared with Comparative Examples 2 and 3, when the Mg content is <4.0wt%, the material strength is insufficient. When the Mg content is greater than 5.0wt%, the material strength is significantly improved, the elongation is reduced, the rivet cracking rate is increased, β phase precipitation forms corrosion channels, and the corrosion resistance decreases. Mn element has the effect of refining grains and improving strength. At the same time, it forms (Fe,Mn)Al6 phase with Fe, which reduces the damage of Fe to ductility and promotes the formation of dense oxide layer. Compared with Comparative Examples 5 and 6, Example 1 showed improved strength due to increased Mn content, but simultaneously decreased elongation and increased cracking rate. However, corrosion resistance was improved; when the Mn content decreased, corrosion resistance significantly declined. Compared with Comparative Example 1, Example 1 showed significantly decreased elongation and increased cracking rate when the Si / Fe ratio was less than 1. An imbalanced Si / Fe ratio easily formed needle-like or lamellar β-AlFeSi phases, which became stress concentration sources, significantly reducing the alloy's ductility and impact toughness. Compared with Comparative Example 4, the addition of rare earth elements and intermediate-process aluminum-titanium-boron wire significantly improved the product's elongation and rivet cracking rate. Each component plays its own role and works synergistically to improve the material's performance; none of the components can be omitted.
[0142] This invention improves product performance by optimizing the production process and heat treatment process. Compared with Comparative Example 11, Example 1 shows that using aluminum-based alloy particles can improve melting efficiency and the uniformity of melt composition during production, reducing performance fluctuations caused by product component segregation. Compared with Comparative Example 7, Example 1 shows that when the casting temperature is below 700℃, the fluidity of aluminum melt deteriorates, inclusions increase, and the cracking rate of rivets increases sharply. Compared with Comparative Example 8, Example 1 shows that removing inclusion defects on the billet surface has a good improvement on product performance. Compared with Comparative Examples 9 and 10, Example 1 shows that different heat treatment temperatures have a significant impact on product performance and stability. Heat treatment temperature and heat treatment time have different degrees of influence on grain size and component segregation. A good heat treatment process plays an indispensable role in rivet performance and production qualification rate.
[0143] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art should understand that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a corrosion-resistant aluminum alloy rivet, characterized in that, Includes the following steps: (1) The aluminum ingots are put into the melting furnace for melting and boronizing treatment, and the first aluminum liquid is obtained after one refining process; (2) Transfer the first aluminum liquid obtained in step (1) to a heat preservation furnace, and add various aluminum-based alloy particles containing silicon, iron, magnesium, manganese, chromium, zirconium, rare earth element cerium and lanthanum in proportion to obtain the second aluminum liquid; (3) The second aluminum liquid obtained in step (2) is refined a second time to obtain the third aluminum liquid; (4) Add aluminum-titanium-boron wire to the third aluminum liquid obtained in step (3), and obtain the fourth aluminum liquid after degassing and filtration; (5) The fourth aluminum liquid obtained in step (4) is continuously cast under the conditions of casting temperature of 710-730℃, casting speed of 2.8-3.0t / h, cooling water temperature of 20-40℃ and billet temperature of 450-470℃ to obtain aluminum billet; (6) The surface of the aluminum billet obtained in step (5) is treated by a milling machine to obtain the billet; (7) Roll the billet obtained in step (6) at a rolling temperature of 400-450℃ and a take-off temperature of 180-220℃ to obtain a corrosion-resistant aluminum rod with a nominal diameter of 9.00±0.3mm. (8) The corrosion-resistant aluminum rod with a nominal diameter of 9.00±0.3mm obtained in step (7) is subjected to a first drawing process to obtain a corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25±0.02mm; (9) The corrosion-resistant aluminum alloy wire with a nominal diameter of 6.25±0.02mm obtained in step (8) is heat-treated at 410-440℃ to obtain aluminum alloy wire. (10) The aluminum alloy wire obtained in step (9) is subjected to a second drawing process to obtain an aluminum alloy wire with a nominal diameter of 6.10±0.02mm; (11) After cutting the aluminum alloy wire with a nominal diameter of 6.10±0.02mm obtained in step (10), cold heading is performed to obtain the corrosion-resistant aluminum alloy rivet. The corrosion-resistant aluminum alloy rivet contains 0.20-0.25wt% Si, 0.15-0.20wt% Fe, 4.3-4.5wt% Mg, 0.8-0.9wt% Mn, 0.10-0.15wt% Cr, 0.15-0.20wt% Zr, 0.1-0.2wt% Ce+La, 0.01-0.015wt% Ti, with the remainder being Al and unavoidable impurities, and the Si / Fe ratio is ≥1.
2. The preparation method according to claim 1, characterized in that, In step (1), aluminum ingots with a purity of not less than 99.7% are added to a smelting furnace and heated to melt. Aluminum-boron alloy is added for boronizing treatment. Under the condition of holding at 750-780℃, a refining agent is blown in with nitrogen to perform a first refining process to obtain the first aluminum liquid.
3. The preparation method according to claim 1, characterized in that, In step (2), the temperature in the heat preservation furnace is 720-740℃.
4. The preparation method according to claim 1, characterized in that, In step (2), the aluminum-based alloy particles are obtained by melting and granulating an aluminum-based master alloy.
5. The preparation method according to claim 1, characterized in that, In step (2), the particle size of the aluminum-based alloy particles is 5-10 mm.
6. The preparation method according to claim 1, characterized in that, In step (3), the temperature of the secondary refining is 720-740℃.
7. The preparation method according to claim 1, characterized in that, In step (4), the third aluminum liquid in the heat preservation furnace is poured into the flow channel, and aluminum-titanium-boron wire is fed before entering the degassing box. Then, it is degassed and filtered in sequence through the degassing box and the filter box to obtain the fourth aluminum liquid.
8. The preparation method according to claim 1, characterized in that, In step (6), a milling machine is used to remove the burrs, cracks, shrinkage and oxide scale generated on the surface of the aluminum billet obtained in step (5).
9. The preparation method according to claim 1, characterized in that, In step (9), the heat treatment time is 6-8 hours.
10. A corrosion-resistant aluminum alloy rivet obtained by the preparation method according to any one of claims 1-9.